Tests on shaped compensators used in heating systems made of chlorinated polyvinyl chloride – CPVC - Rubnikowicz, Adam; Sabiniak, Henryk (Instal, 2020)
The use of plastic materials has become a standard in sanitary systems design. Due to numerous advantages of polymers, heating and hot water systems made of them have become an alternative to the ones made of traditional materials such as steel or copper. The values of forces working on particular elements of compensators as well as their displacement result from linear thermal elongation of segments of the system mounted in fixed supports. The article presents theoretical considerations on the subject of linear elongations and stress in shaped compensators that occur during exploitation of heating systems made of chlorinated polyvinyl chloride – CPVC. In order to verify the results of the theoretical considerations, both the analytical and the numerical ones, a series of fatigue and destruction experiments were performed in the next stage of the research.